The effect of the manipulation of certain linguistic variables on language comprehension in Alzheimer's Disease - Jones, Dilys Margaret (My University, 2007)
Comprehension was assessed under various conditions in nine subjects with probable Alzheimer’s Disease. Four linguistic variables were selected, namely syntactic complexity, the use of pronouns, directness and literality. Each variable was assessed in sentences in a simple form and in a complex form. Discourse passages which included all of the variables were then constructed, and these tasks were also administered in simple and complex forms. All subjects performed qualitatively and quantitatively better under the simple conditions than under the complex for all four of the variables assessed. However, this effect was more marked in the sentence tasks than in the discourse tasks. Furthermore, individual subjects responded differently to the manipulation of the variables. Results of the study suggest that modifying the variables investigated can improve the comprehension of people with moderate to severe Alzheimer’s Disease. This has important implications for the training of caregivers and conversational partners, and suggests that this type of indirect intervention may be an effective way for speech therapists to provide clinical services to people with dementia in South Africa.
Student Number: 8402734 Master of Arts (Speech Pathology) Faculty of Humanities
Keywords: Linguistic variables; Language comprehension; Alzheimer's Disease; Syntactic complexity; Training of caregivers; Conversational partners